Finance and Development, December 1995. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1995)
WHAT early warning signals should policymakers heed to avoid a repeat of a Mexico-type reversal of private capital flows? Experience suggests that a combination of indicators can provide powerful hints of approaching problems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet